Contaminazione ambientale ed elaborazione del rischio sanitario: i costi dell’incertezza. Una ricerca antropologica sul “gass-ra-doon” nel quartiere “Tamburi” (Taranto) - Enzo V. Alliegro (Archivio Antropologico Mediterraneo)
In September 2018, the Agenzia Regionale per la Protezione dell’Ambiente di Puglia (“Apulia Regional Agency for the Preservation of the Environment”) detected a very high concentration of radon, a carcinogenic agent, in the schools of Tamburi, an area of Taranto. Based on the comparative use of numerous documentary sources and intense field research conducted in an industrialized town with a very high awareness of health risks, the study tackles the problem of the relationship between health and environment protection public bodies and the reactions of the people who live in the area. Moreover, starting from the analysis of contextual and symbolic aspects, the article focuses on the concept of risk perception showing that it is the product of a process of elaboration that configures syncretic and contingent constructions.